Papaya Fruit Fly, Toxotrypana curvicauda Gerstaecker (Insecta: Diptera: Tephritidae) - H. Lane Selman; John B. Heppner; Thomas R. Fasulo (EDIS, 2012)
The papaya fruit fly is the principal insect pest of papaya throughout the tropical and subtropical areas of the New World. The insect was introduced into Florida in 1905, most likely from the West Indies on papaya shipments. It first became established in the Florida Keys and Miami, then spread throughout the state wherever papayas are grown. Papaya fruit fly larvae and adults have been found in Florida in every month of the year. This revised 6-page fact sheet was written by H. L. Selman, J. B. Heppner, and T. R. Fasulo, and published by the UF Department of Entomology and Nematology, January 2012.